RANCANG BANGUN SISTEM INFORMASI NILAI UJIAN SISWA SMP NEGERI 3 BUMIAYU BERBASIS WEB - Mulia Rahmayu (Universitas Bina Sarana Informatika, 2015)
The development of education in Indonesia is very encouraging, as evidenced by a press conference Kementrian Pendidikan and Kebudayaan exam results are released National Junior High School (SMP) in 2012/2013 as much as 99.55 percent passed the National Examination. As for the website as an information medium is a technology that was created to facilitate human obtain information quickly. SMP Negeri 3 Bumiayu a school that requires an online examination system announcements, both national exams and school exams. As well as systems that can provide information to the general public, for which the author tries to make the final exam scores of students information system in SMP Negeri 3 Bumiayu which until now has not used the media test website for announcements. Graduation delivery systems is still manually start recording student data, the data value of the test, both national exams and school exams where the guardians of students taking the exam results to the school when the announcement of the National Examination or when the announcement of exam school homeroom test result sheet distributed to students. The design of the information system is the best solution to solve the existing problems in this school. This online system is better than the manual system so that information obtained faster and more effective and efficient than the previous system.Keywords: Design, Information Systems, Value Test, Website